Ethnic Interest Groups in US Foreign Policy-Making A Cuban-American Story of Success and Failure - Rytz, Henriette M.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This book comprises the first systematic study on the impact of ethnic interest groups on US foreign policy, using the case study of how the Cuban?American National Foundation (CANF) influenced the outcome of three different legislatives debates that directly affected US Cuba policy.
Keywords: Political science; Political theory; Europe -- Politics and government; International relations; Political philosophy; Ethnicity; European Politics; Ethnicity Studies